Sustainable management of agro-industrial by-products and technological bioconversion strategies - Debernardi-Vázquez, Teresita de Jesús; Aguilar-Rivera, Noé (Revista Colombiana de Investigaciones Agroindustriales, 2020)
In order to evaluate sustainable strategies to obtain solid biofuel and fertilizers from agroindustrial by-products in contrast to the agroecological zoning and expansion of crops in Veracruz, Mexico, drying methods with orange peels, sugarcane bagasse and crop residues were tested. The experiments to obtain a solid biofuel with 12.28% humidity in 30 days. Six fertilizer production treatments in plastic containers from 30 to 90 days were evaluated using by-products: orange peel, cachaça, stillage, molasses, ashes, manure, sugar cane crop residues and edible mushroom production through composting techniques, vermicomposting and bocashi. Fertilizers with pH between 5.4 and 12.0, 3% to 70% of M.O. and C / N ratio from 8 to 40. The agroecological zoning was carried out with the Maxent software, determining that the geographic regions with the greatest aptitude for citrus and sugar cane crops are located in the Mexican southeast and in particular the state of Veracruz. For sugarcane, the limiting factors for productivity as raw material for biorefineries are related to access to water (rainfall) and explain 57.1% of the simulation. In the case of citrus, the factors are related to temperature, rainfall and topography, which together impact 44.5%.